A pathologic case of gout tophi deposition with a concurrent systemic bacterial infection in a leopard gecko (Eublepharis macularius) - Mazlan, Mazlina; Syafiq, Mohd Asrul; Zakaria, Muhamad Alif; Abdul Samad, Luqman; Che' Amat, Azlan (Scienceline Publication, 2023)
Gout is caused by excessive uric acid in the blood deposited in tissues (visceral gout) or joints (articular gout), leading to severe inflammation and pain. A female leopard gecko was presented to the University Veterinary Hospital, University of Putra, Malaysia, with a history of swelling at the left caudal mandible, inappetence, and weight loss. An oral examination indicated a swollen mouth with scabs on the upper right mandible and multiple whitish deposits inside the mouth. The preliminary diagnosis was mouth rot, and the treatment included metronidazole and a multivitamin supplement. The leopard gecko died 12 days after treatment since there was no improvement. Post-mortem examination revealed that the liver was slightly enlarged with generalized moderate congestion and the presence of whitish deposits, as well as noticeable whitish deposits on the pleural surface of the lungs. Histopathological examination of the lungs revealed a granuloma with an inflammatory reaction predominantly by abundant mononuclear cells and fibrin deposition. An irregular collection of amorphous materials in the visceral pleura suggested gout tophi. The liver was infiltrated with amorphous material and fibrinous tissue, and it had mild congestion, indicating visceral gout and bacterial infection. Klebsiella pneumoniae and Proteus mirabilis were isolated from the lungs and liver samples, respectively. In conclusion, gout tophi is common in reptiles, but visceral involvement is rare, and early detection is critical to avoid secondary bacterial infection, as demonstrated in this case.